Trabalho e capital na Amazônia Oriental: movimento operário versus reestruturação produtiva no Complexo Albrás-Alunorte: 1990 – 2005 - SANTIAGO, João Carlos da Silva (Universidade Federal do Pará, 2014)
The present dissertation studies the productive restructuration in the factories of ALBRAS and ALUNORTE, situated in the municipal district of Barcarena/PA, and how the working class movement has put itself against this process, from 1990 to 2005. Through a study of the chronic crisis of the worldwide capitalist economy, worsened by the two petroleum crash, it attempts to explain how the installation of two modern factories in the Oriental Amazon, with a working class contingent highly concentrated. It is emphasized how important is the role of the State to the achievement of this process. We also analyze how, since the “globalization” phenomenon – which is a higher stage of the imperialism -, and the new work organization process – mainly the toyotist model -, the working class movement and its organizations were put to the proof because of the flexibilization of the work, the precarization and the subcontraction, which have made difficult the strikes and the class movements in Brazil and in the world, in the 1990s. Based in bibliographic material, brochures and interviews with workers and directors of labor unions, the study evidences that the struggles against the productive restructuration in ALBRAS was more intense, including the strike mode, than in ALUNORTE, because ALBRAS was ten years ahead of ALUNORTE and it was the first laboratory of CVRD in the city of Barcarena. Contradictorily, it was in ALBRAS where occurred the highest number of dismissals in the studied period, before and after the privatization of CVRD. The dissertation aims to show the role of the Chemists and Metallurgists Labor Union in this process of struggles against the productive restructuration in the factories of ALBRAS and ALUNORTE.